Studies towards the total synthesis of simonsol A - Boden, Grace (2021)
Neolignans are secondary metabolites found in plants from the genus Illicium and investigations into their bioactivity have shown them to possess medicinal properties. Dunnianol, a sesquineolignan, has shown neurotrophic activity in the promotion of neurite outgrowth. We hypothesised that the biosynthesis of simonsol A is derived from dunnianol and this report focusses on the comparison between the two compounds and describes the synthesis towards simonsol A. An intermediate towards the synthesis of simonsol A was prepared through a microwave-assisted Suzuki-Miyaura cross-coupling reaction, followed by allylation of the phenolic core in 50% yield over 4 steps. Computational studies of the relative energies for the interconversion provide strong evidence towards the newly proposed biosynthesis of simonsol A. The energy barrier of the Claisen rearrangement was found to be 45.6 kcal/mol and for the Cope rearrangement, 32.5 Kcal/mol.